Pengembangan Ekosistem Kewirausahaan melalui Kemitraan dengan Dunia Usaha dan Industri - Fortunisa, Ananda (Indonesian Journal for Social Responsibility, 2022)
Economic cycle, such as employment, monetary cycle, local product, and other aspects of the economy in Indonesia are currently decline due to low entrepreneurial growth from the community. The purpose of this community service activity is to accelerate the level of literacy about the sustainability of entrepreneurship which is influenced by the surrounding business ecosystem, such as cooperation or partnership programs built from all actors or stakeholders. Therefore, this community service activity is carried out by seminars and online literacy enrichment methods to increase awareness and skills of entrepreneurial and business stakeholders to map, design, and build business partnership concepts, so that the entrepreneurial ecosystem can run sustainably, and win-win solution among stakeholders. The results of this activity, it was found that there was a lack of understanding of the participants to design and build partnerships in their entrepreneurship, so it is recommended that seminars, training and enrichment activities be carried out more often, so that various types of partnership programs can grow and develop. After this activity was carried out, the participants became more skilled in mapping, designing and building their partnership program with all stakeholders.